2017
DOI: 10.1038/s41598-017-07787-4
|View full text |Cite
|
Sign up to set email alerts
|

HuR-targeted small molecule inhibitor exhibits cytotoxicity towards human lung cancer cells

Abstract: Human antigen (Hu) R is an RNA-binding protein whose overexpression in human cancer correlates with aggressive disease, drug resistance, and poor prognosis. HuR inhibition has profound anticancer activity. Pharmacologic inhibitors can overcome the limitations of genetic inhibition. In this study, we examined the antitumor activity of CMLD-2, a small-molecule inhibitor directed against HuR, using non-small cell lung cancer (NSCLC) as a model. CMLD-2 efficacy was tested in vitro using H1299, A549, HCC827, and H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…In contrast, our data support a tumour suppressor role for miR-19b in breast epithelial cells, in accordance with some data in prostate cancer (Ottman et al, 2016) and hepatocellular carcinoma (Hung et al, 2015). HuR has also been defined as an oncogene, with higher expression associated with poor survival in breast and other cancers (Zhu et al, 2013, Denkert et al, 2004, and it is the focus of ongoing work to develop novel targeted therapeutics (Huang et al, 2016, Muralidharan et al, 2017, Wu et al, 2015. Strangely, expression levels of HuR and P-gp have previously been shown to correlate positively in breast cancer (Zhu et al, 2013), in direct contrast to the regulation we have identified, although this previous observation may be compromised by the lack of antibody validation.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, our data support a tumour suppressor role for miR-19b in breast epithelial cells, in accordance with some data in prostate cancer (Ottman et al, 2016) and hepatocellular carcinoma (Hung et al, 2015). HuR has also been defined as an oncogene, with higher expression associated with poor survival in breast and other cancers (Zhu et al, 2013, Denkert et al, 2004, and it is the focus of ongoing work to develop novel targeted therapeutics (Huang et al, 2016, Muralidharan et al, 2017, Wu et al, 2015. Strangely, expression levels of HuR and P-gp have previously been shown to correlate positively in breast cancer (Zhu et al, 2013), in direct contrast to the regulation we have identified, although this previous observation may be compromised by the lack of antibody validation.…”
Section: Discussionsupporting
confidence: 90%
“…Actinomycin D (Sigma) was dissolved in Dimethyl sulfoxide (DMSO) and used at the final concentration of 5 µg/mL. The HuR inhibitor, CMLD-2, was synthesized and used as previously described [43,54]. The compound was dissolved in DMSO and used in the studies described herein.…”
Section: Plasmids and Reagentsmentioning
confidence: 99%
“…Unsurprisingly, knockdown of HuR is an established means to reduce anchorage‐independent growth and oncogenic potential of at least some sets of cancer cells . The disease relevance of HuR has propelled efforts to identify small‐molecule inhibitors of HuR, which have yielded some initial hits that show potential promise as useful therapeutics . These molecules mostly appear to interfere with HuR dimerization, which is essential for HuR function .…”
Section: Introductionmentioning
confidence: 99%